Decommissioning of large offshore structures – The role of an Independent Review Group (IRG). (1st February 2016) - Wilkinson, W.B.; Bakke, T.; Clauss, G.F.; Clements, R.; Dover, W.D.; Rullkötter, J.; Shepherd, J.G.
Abstract: Most proposals for the construction or decommissioning of large offshore structures will need to address a range of issues including the use of innovative technologies, environmental impact, health and safety risks, regulatory requirements and public acceptability. Usually, several options will be examined and run through a Comparative Assessment before a final selection. There is also the need to keep stakeholders informed as the project proposals develop. Many of the issues require complex scientific or engineering studies and risk assessments frequently outsourced to contractors. The information in their reports feeds the Comparative Assessment. However, it may be difficult for stakeholders, or even the regulating agency, to judge the veracity of such technically complex issues and feel confident that the evidence for the final project proposal is soundly based. Failure to adequately exchange information has led to open confrontation in the past. An approach which can provide greater transparency and confidence in the outcome is to set up a review group of independent professionals with wide expertise at the outset of a project. This paper discusses the benefits of an Independent Review Group (IRG) to the Commissioning Organisation, regulating authorities, the industrial sector and stakeholder public interests, and describes the experience of the authors with such a body. Abstract : Highlights: Independent Review Group (IRG) adds quality audit to offshore commissioning. IRG studies spread of options and worth/validity of Comparative Assessments. IRG provides interface between stakeholders and Commissioning Organisation. IRG will act fully independently, based on clearly defined terms of reference. IRG final report will focus on the evidence base of the selected option(s).